Generalized Trapezoidal Fuzzy Numbers: A New Approach to Ranking - Lakshmi,; M. Suresh, (The journal of contemporary issues in business and government, 2019)
Fuzzy numbers play an essential part in decision making, optimization, forecasting, and other areas of analysis. Prior to taking action, fuzzy numbers must be rated by an executive. The ranking approach presented by Chen and Chen (Expert Systems with Applications 36 (2009) 6833-6842) is shown to be wrong in this work using various counter instances. New methods for ranking generalised trapezoidal fuzzy numbers are the focus of this study. Because the suggested technique provides the right ordering of generalised and normal trapezoidal fuzzy numbers, it is a significant benefit. According to Wang and Kerre's (Fuzzy Sets and Systems 118 (2001) 375- 385), the suggested ranking function meets all the acceptable features of fuzzy quantities. Keywords—Ranking function, Generalized trapezoidal fuzzy num- bers